Strategies To Improve The Quality of Education Through The Optimization of Minimum Service Standards - Lely Nurarifah; Darusalam (International Journal of Advanced Studies in Educational Management (IJASEM), 2025)
The current problem is that the implementation of SPM Education has not been implemented optimally. Thus, further research needs to be done about SPM Pendidikan if implemented in Islamic educational institutions to improve the quality of education. This research is important to be carried out so that Islamic educational institutions are able to implement SPM Education optimally. The method used in this study is qualitative with a Literature Study research approach. The source of this research data is obtained from books, scientific articles, and government regulations. Government regulations, namely Government Regulation Number 2 of 2018 concerning Minimum Service Standards and supported by Permendikbudristek Number 32 of 2022 concerning Technical Standards for Minimum Education Services, are the main references. MAN 2 Kota Malang is one of the Islamic educational institutions that implements SPM Education through quality standards in the aspects of input, process, and output. The implementation of SPM Pendidikan policy in educational institutions is closely related to the quality of these educational institutions, so that SPM Education can be applied by determining quality standards to realize the quality of educational services.